PHYTOCHEMICAL AND ANTIBACTERIAL ACTIVITY OF Cochlospermum tinctorium ROOT POWDER AGAINST FOODBORN PATHOGENS - Jodi, S. M.; Sani, N. A. (FUDMA Journal of Sciences, 2022)
The plant Cochlospermum tinctorium is a sub-shrub that belongs to the family Cochlospermaceae. The plant has been used in traditional medicine for the treatment of malaria, rickets, stomachache, diarrhea, gastric ulcer, parasitic infestations, liver diseases, fever, pain, inflammation, infectious diseases, epilepsy, snake bite, burns, orchitis, labour, menstrual problems, and many other diseases. The aim of study was to evaluate the phytochemical composition and antibacterial activity of Cochlospermum tinctorium against Staphylococcus aureus, Escherichia coli and Klebsiella procured from Microbiology Research Laboratory Sokoto State University Sokoto. The root powder of Cochlospermum tinctorium was collected from the market, Tambuwal Local Government Area of Sokoto State, Nigeria. Cooled extraction method was used for extraction using methanol and aqueous as solvent. The antibacterial activity of the plant was determined on Mueller Hinton agar using agar well diffusion method. Furthermore, the Minimum Inhibitory concentration (MIC) and Minimum Bactericidal Concentration (MBC) of plant extract against the isolate were also investigated.